SARS-CoV-2 infection in children with cystic fibrosis: Experience of a Portuguese reference centre - Moreira, Mafalda (2022)
Introduction: Respiratory viruses are often responsible for pulmonary exacerbations and increased morbimortality in patients with cystic fibrosis (CF). For this reason, SARS-CoV-2 was expected to have a significant impact on the respiratory status of these patients, especially in those at risk. Detailed data of the clinical course of COVID-19 in children with CF is scarce. Objectives: The aim of this study was to determine the incidence, clinical characteristics, and course of COVID-19 infection in pediatric patients with CF. Material and methods: This was a retrospective observational study of children with CF and SARS-CoV-2 infection followed at a Portuguese reference centre between March 2020 and March 2022. Results: Twelve of 30 children with CF were infected by SARS-CoV-2 (40%), in a total of 13 episodes. The median age was 10.5 years, and 33% were male. Most cases (69%) occurred between January and March 2022, when Omicron was the predominant variant. The infection rate was higher in children not fully vaccinated. None of the children with additional risk factors was infected. Ninety-two percent of patients presented with mild disease and one child with low body mass index was hospitalized with pneumonia. None required oxygen therapy or admission to the Intensive Care Unit. No cases of mortality were reported. Eighty-three percent of patients fully recovered after two months of follow-up. Discussion: In this first national study of children with CF and COVID-19 infection, most children presented with mild disease and could be safely managed at home. Conclusion: This study is in line with the few evidence available in the literature and contributes to a better understanding of SARS-CoV-2 infection in children with CF during predominance of the Omicron variant, providing additional data that can guide families and clinical teams in the management of patients.